The Taxpayer Protection Amendment: A Preliminary Analysis - Reschovsky, Andrew (My University, 2006)
This analysis demonstrates that a proposed amendment to Wisconsin's constitution to limit the annual growth of government revenue would reduce public services and harm economic development. If it had been enacted in 1985 and not changed, Wisconsin would have experienced a 30 percent decrease in its revenue from taxes, bonds and fees.